Blood Transfusion Reactions in Elderly Patients Hospitalized in a Multilevel Geriatric Hospital - E. Lubart; R. Segal; N. Tryhub; E. Sigler; A. Leibovitz (Journal of Aging Research, 2014)
Background/Objectives. Blood transfusion is a critical issue for patients with chronic diseases such as heart failure, chronic kidney disease, and malignancy. However, side effects are not rare. The purpose of the study is to evaluate the frequency of adverse blood transfusion reactions in hospitalized elderly patients during a one-year period. Design/Setting/Participants. Blood transfusion reactions such as fever, chills, dyspnea, and others following blood transfusions in hospitalized geriatric patients during one-year period were examined. Results. 382 blood units (242 patients) were administered during the study period. In 40 (11%) cases, blood transfusion reactions occurred. Fever was the most common reaction in 29 cases (72%), four (10%) had shortness of breath, and 3 (8%) had vomiting and chills each. There were no lethal cases in the 24-hour period following blood transfusions. Conclusion. A relatively low rate of adverse blood transfusion reactions occurred in our geriatric patients. We may speculate that this is related to underreporting of minor symptoms due to the high percentage of demented patients in this population.